Lynch Syndrome Associated with Two MLH1 Promoter Variants and Allelic Imbalance of MLH1 Expression. Issue 6 (17th April 2015) - Hesson, Luke B.; Packham, Deborah; Kwok, Chau‐To; Nunez, Andrea C.; Ng, Benedict; Schmidt, Christa; Fields, Michael; Wong, Jason W.H.; Sloane, Mathew A.; Ward, Robyn L.
<x xml:space="preserve">Abstract</x> We identified two families with suspected Lynch syndrome associated with a variant haplotype at the MLH1 gene promoter (c.‐28A>G and c.‐7C>T). This variant haplotype is associated with partial loss of MLH1 expression in the absence of DNA hypermethylation or alterations in nucleosome positioning. Our findings suggest one or both of these non‐coding variants most likely affect MLH1 expression through altered binding of an unidentified transcriptional regulator.